Immunological Significance of HMGB1 Post-Translational Modification and Redox Biology - Kwak, Man Sup; Kim, Hee Sue; Lee, Bin; Kim, Young Hun; Son, Myoungsun; Shin, Jeon-Soo (Frontiers in Immunology, 2020)
Most extracellular proteins are secreted via the classical endoplasmic reticulum (ER)/Golgi-dependent secretion pathway; however, some proteins, including a few danger-associated molecular patterns (DAMPs), are secreted via non-classical ER/Golgi-independent secretion pathways. The evolutionarily conserved high mobility group box1 (HMGB1) is a ubiquitous nuclear protein that can be released by almost all cell types. HMGB1 lacks signal peptides and utilizes diverse non-canonical secretion mechanisms for its extracellular export. Although the post-translational modifications of HMGB1 were demonstrated, the oxidation of HMGB1 and secretion mechanisms are not highlighted yet. We currently investigated that peroxiredoxins I and II (PrxI/II) induce the intramolecular disulfide bond formation of HMGB1 in the nucleus. Disulfide HMGB1 is preferentially transported out of the nucleus by binding to the nuclear exportin chromosome-region maintenance 1 (CRM1). We determined the kinetics of HMGB1 oxidation in bone marrow-derived macrophage as early as a few minutes after lipopolysaccharide treatment, peaking at 4 hours while disulfide HMGB1 accumulation was observed within the cells, starting to secrete in the late time point. We have shown that HMGB1 oxidation status, which is known to determine the biological activity in extracellular HMGB1, is crucial for the secretion of HMGB1 from the nucleus. This review summarizes selected aspects of HMGB1 redox biology relevant to the induction and propagation of inflammatory diseases. We implicate the immunological significance and the need for novel HMGB1 inhibitors through mechanism-based studies.